Aspectos da formação do estudante de graduação em fonoaudiologia na clínica da voz : por uma abordagem enunciativa Bakhtiniana - Cronemberger, Flávia Fialho (2014)
Therefore, the principal objective of this study was to observe and analyze aspects related to the training process of a group of undergraduate speech therapy students during supervised practice in the field of voice therapy, with a view towards reflecting on the importance of being attentive, within this learning space, to the constitutive socio-historicity of the subjects participating in it. This was a longitudinal, qualitative study based on Bakhtinian principles as applied to studies in the field of human sciences. The study included filmed recordings of supervised sessions and of some clinical visits, as well as interviews held with a group of female students, two professors and two patients, all of whom participated in a supervised training course for one semester (the second semester of 2011) in an institute of higher education. Of the recordings and observations made, utterances made by one of the professors, a group of female students and one of the patients during a clinical visit were selected and analyzed. Based on this analysis, intertwined voices (of the academic-scientific history of speech therapy, of the professor, of the students, of the patient, etc.) were found, reflecting more valuations of the organicist/technicist conception throughout the training period analyzed. It was found that the student speech therapists gave little importance to listening to the voices of the patient during therapy, either in their understanding of clinical treatment as a space in which the organicist theory is strengthened or when attempting to observe the subject in a fragmented (biologizing) manner rather than in his/her constitutive complexity. It was found that the student speech therapists gave little importance to listening to the voices of the patient during therapy, since they understood clinical treatment as a space in which the organicist theory is given greater weight; hence they observed the subject in a fragmented (biologizing) manner rather than in his/her constitutive complexity. It is possible that, when incorporated into voice therapy training, the Bakhtinian concepts of discourse and utterance will help improve students understanding of the singularities and complexities involved in each therapeutic process, including those that deal with the biologizing approach of each subject, thus contributing towards rendering clinical visits and supervisions more effective.